Implementasi Program Literasi dalam Meningkatkan Minat Baca Peserta Didik di SDN Unggulan Bontomanai (INDONESIAN LANGUAGE TEACHING & LITERATURE JOURNAL, 2023)
This study aims to describe the form, implementation and impact of the literacy programme implemented at SDN Unggulan Bontomanai, Bontomarannu Sub-district, Gowa Regency. The research data was obtained from interviews with teachers, observations and distributing questionnaires to 29 grade V students. Based on the results of interviews and observations, it was found that the form of literacy programme used is reading-writing literacy and its application has three stages, namely the habituation stage, the development stage, and the learning stage. In the habituation stage, students are accustomed to reading or being read books other than textbooks, then discussion activities are carried out related to the books read. At the development stage, literacy implementation is carried out with the aim of consolidating students' interest in reading and increasing students' understanding. At the learning stage, students have been able to capture and re-explain the material provided well. The results of the questionnaire accumulation show that the literacy programme implemented at Bontomanai Primary School has a positive impact, such as reading becoming a student habit, the school library becoming more lively, and the way students think being creative, critical and innovative.